Diversity of freshwater hydrozoans from Neotropical region: an annotated inventory of species - Deserti, María I.; Stampar, Sergio N.; Acuña, Fabián H. (Revista de biología tropical, 2023)
Introduction: Worldwide, six genera of the class Hydrozoa are recognized in continental waters: the cosmopolitan Hydra, the colonial Cordylophora and Pachycordyle, the medusae Craspedacusta and Limnocnida and the little polyp Calpasoma. Even though interest in cnidarians has grown in recent years, those restricted to freshwater continue to be relegated and there is even little published information on the ubiquity of certain species. In the Neotropical region, knowledge about its distribution is still very scarce. Methods: We reviewed the global literature on the subject and different online database platforms, presenting in this work a nomenclator, including discussions of the status of some species and provide the most recent identification key. Results: This analysis reveals that in 15 countries corresponding to the Neotropical region, the finding of freshwater hydrozoans has been reported. Panama, Brazil and Argentina are the countries with the highest number of reports. Conclusions: The heterogenity of environments where these genera have been found (from the Strait of Magellan to Mexico) offers a clear vision of their wide distribution and great adaptability to different environments. This study evidence the knowledge gap that still exists about the Neotropical freshwater hidrozoans and the importance of systematizing the current information about their distribution, biology and ecology, especially for those species considered invasive.